Muzakki’s Perception Regarding the Implementation of the NIK to Replace NPWZ - Kurniawan, Rizaludin (International Journal of Zakat, 2024)
This study aims to analyze muzaki perception of the discourse on the integration of NPWZ as NIK and review whether this integration can fulfil the principles of simplicity, benefit, and safety from risk. This study adopted Technology Accaptance Model (TAM) and modified Innovation Difussion Theory (IDT), employed several variables namely perceived ease of use, perceived usefulness, and perceived safety risks. The premier data from 137 respondents who was BAZNAS muzakki were collected then analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS) wiht SmartPLS application. In general, the result of hypothesis testing proves that perceived ease of use, perceived usefulness, and perceived safety from risk significantly affect Muzakki's intention to use NIK in a positive way. This study also found that Perceived Ease of Use (PEU) is considered the main contributor affecting Muzakki's intention to use NIK as the replacement for NPWZ, while Perceived Safety from Risks (PSR) is the latent variable with the lowest percentage